Fuzzy sets and fuzzy logic in multi-criteria decision making. The 50th anniversary of Prof. Lotfi Zadeh’s theory: introduction - Herrera-Viedma, Enrique (Technological and Economic Development of Economy, 2015)
„Fuzzy sets and fuzzy logic in multi-criteria decision making. The 50th anniversary of Prof. Lotfi Zadeh’s theory: introduction" Technological and Economic Development of Economy, 21(5), pp. 677–683